Labour Markets, Flexible Specialization and the New Microcorporatism: The Case of Canada's Major Appliance Industry - Wells, Don (Relations industrielles / Industrial Relations, 2001)
"High performance" management systems in unionized workplaces have the potential to create a more microcorporatist workplaces have the potential to create a more microcorporatist industry relations system in Canada. Microcorporatist tendencies reflect more active worker cooperation in achieving management productivity, quality and flexibility goals. Analysis of development of these tendencies in the major appliance industry suggests that microcorporatism has contradictory implications. In one direction lies the displacement labor politics by a local-centered unionism that is increasingly captured by the logic of market competition. In a second direction lies a logic of greater worker resistance related to increased worker control of labor processes.
Keywords: Appliance industry; Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; LABOR market; Labor Unions; Labor relations; Management styles; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Studies